Statistical and linguistic methods for the recognition of automatically generated texts - Lukashevskyj Arsenij; Khairova Nina (онлайн, 2022)
This article is devoted to a detailed study of methods for determining machine-generated texts, a review of linguistic models trained on the publicly available sources, and a research of the problems associated with this.